Bizarre-Privileged Items in the Universe : The Logic of Likeness - North, Paul, 1971- (Book collections on Project MUSE., 2021)
"This book affirms the experience of likeness at the heart of many, if not all, disciplines of knowledge and seeks to formalize that basic experience into a science of its own, "homeotics.""--